Exosomes: A Potential Key Target in Cardio-Renal Syndrome - Gonzalez-Calero, Laura; Martin-Lorenzo, Marta; Alvarez-Llamas, Gloria (Frontiers in Immunology, 2014)
Exosomes have proven roles in regulating immune response, antigen presentation, RNA and protein transfer, and cell–cell (organ–organ) interaction/signaling. These microvesicles can be considered a mechanism of non-classical secretion of proteins, and they represent a sub-proteome, thus assisting in the difficult task of biomarker discovery in a biological fluid as urine, plasma or serum. A potential role of exosomes in the cardio-renal syndrome is currently underexplored. Cardiovascular disease (CVD) continues to be the leading cause of morbidity and mortality worldwide and, particularly, rates of cardiovascular events and death consistently increase as kidney function worsens. In other words, chronic kidney disease acts as a risk multiplier. Unfortunately, the relationship between markers of cardiovascular risk in kidney pathology often differs from that in the general population. Efforts in the search for novel action mechanisms simultaneously operating in both pathologies are thus of maximum interest. This article focuses to the role of exosomes in cardiovascular and renal diseases, in the search for novel key targets of interaction between heart and kidneys.